MBSE Enabled Trade‐Off Analyses. Issue 1 (20th September 2021) - Parnell, Gregory S.; Shallcross, Nicolas; Specking, Eric; Phillips, Matthew
Abstract: This paper examines the potential to use Model‐Based Systems Engineering (MBSE) tools to perform trade‐off analysis of alternative systems decisions in the system life cycle from the concept stage to the retirement stage. Specially, we searched for integrated models that automate the simultaneous evaluation of the performance, effectiveness, stakeholder value, and cost of multiple alternative system designs. We used the Web of Science to perform a literature search to identify published papers that describe the use of MBSE tools to support automated analysis of alternatives and trade‐off analyses. We found very few papers that claimed to use MBSE to provide analysis of design alternatives or tradespace exploration. Based on the literature search insights, we identify and describe the required and desired capabilities to perform automated trade‐off analyses of performance, effectiveness, stakeholder value, and cost for multiple system design alternatives using integrated models.